Female orgasm and menopause - Łukasiewicz, Monika; Lew-Starowicz, Zbigniew (Menopause Review/Przegląd Menopauzalny, 2008)
Mood disturbances and sexual dysfunction which often occur during menopause transition may impair personal life. Based on findings from the National Health and Social Life Survey, female orgasmic disorder is the second most frequently reported sexual problem. It results not only from hormonal changes and psychosocial factors, but also from relationship aspects. Orgasmic problems can be treated with cognitive-behavioural therapy. So far there is no pharmacological agent registered directly for this dysfunction. However, there is evidence, which should be proved in further research, that adding testosterone to HT has a beneficial effect on sexual function in postmenopausal women.